2017
DOI: 10.1200/jgo.2016.005595
|View full text |Cite
|
Sign up to set email alerts
|

Prediagnostic Intervals in Retinoblastoma: Experience at an Oncology Center in Brazil

Abstract: PurposeRetinoblastoma is the most common intraocular malignancy of childhood. In most cases, parents are the first to notice leukocoria and other symptoms before undergoing a prolonged period of stress before diagnosis. The purpose of this study was to determine prediagnostic intervals of patients with retinoblastoma at an oncology tertiary center (Instituto Nacional de Cancer) in Rio de Janeiro, Brazil, and relate them to stage at diagnosis, eye salvage, and survival.MethodsParents or caregivers of children w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 36 publications
(51 reference statements)
1
14
0
Order By: Relevance
“…RB is usually diagnosed at later ages in developing countries. In our study, the mean age of RB cases was 21.8 months similar to the results from the study of Mattosinho et al from Brasil with a mean age of 21.7 months [ 5 ]. On the other hand, Gallie et al reported that the mean age at diagnosis was 12 and 9 months for North America and Europe, respectively [ 6 ] and Shields et al reported a mean age of 18 months from USA [ 7 ].…”
Section: Discussionsupporting
confidence: 90%
“…RB is usually diagnosed at later ages in developing countries. In our study, the mean age of RB cases was 21.8 months similar to the results from the study of Mattosinho et al from Brasil with a mean age of 21.7 months [ 5 ]. On the other hand, Gallie et al reported that the mean age at diagnosis was 12 and 9 months for North America and Europe, respectively [ 6 ] and Shields et al reported a mean age of 18 months from USA [ 7 ].…”
Section: Discussionsupporting
confidence: 90%
“…There were 46 patients (50.5%) with parents of middle social status, and 45 patients (49.5%) with middle to low social status. In developed countries such as America, Britain, and other European countries, this malignancy is diagnosed earlier in childhood less <2 years [5,6]. In developing countries, RB is diagnosed in older children.…”
Section: Discussionmentioning
confidence: 99%
“…The RB incidence varies according to the sociodemographics of each country [3-5] Parental education, low socioeconomic conditions, and inadequate health facilities may result in delays of diagnosis and management of RB in developing countries. In developed countries such as America, Britain, and other European countries, this malignancy is diagnosed earlier in childhood <2 years [6].The RB incidence is 1: 15.000-20.000 per birth rate. This cancer generally occurred unilaterally, the mean age when diagnosed was two years in 60% of cases [4].…”
mentioning
confidence: 99%
“…17 In Brazil, maternal education carried a significant difference with outcomes (advanced stage at diagnosis, enucleation and survival). 18 Interestingly, low SES per se was not associated with poorer outcomes.…”
Section: Discussionmentioning
confidence: 95%